2021
DOI: 10.1097/md.0000000000027638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tofogliflozin on adrenocorticotropic hormone, renin and aldosterone, and cortisol levels in elderly patients with diabetes mellitus

Abstract: Adrenocorticotropic hormone (ACTH) and cortisol reportedly play a role in glycemic control in patients with type 2 diabetes mellitus (T2DM); however, the underlying mechanism remains controversial. We retrospectively investigated the effect of tofogliflozin on serum ACTH and cortisol levels in elderly patients with T2DM.Patients received 20 mg tofogliflozin daily for 3 months. Serum ACTH and cortisol levels were measured at baseline, as well as after 1 month and 3 months of tofogliflozin therapy.Serum ACTH lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…actions [ 121 ]. It was recently reported that the SGLT-2 inhibitor tofogliflozin decreased serum ACTH and cortisol levels in subjects with type 2 diabetes, indicating that tofogliflozin also influences the HPA axis [ 122 ]. Moreover, metformin, an insulin-sensitizer used as the first-line drug for treating type 2 diabetes, does not only lower plasma insulin and glucose levels, but also can reduce ACTH levels and cortisol [ 123 , 124 ].…”
Section: Can Hyperinsulinemia-induced Activation Of the Hpa Axis Be M...mentioning
confidence: 99%
“…actions [ 121 ]. It was recently reported that the SGLT-2 inhibitor tofogliflozin decreased serum ACTH and cortisol levels in subjects with type 2 diabetes, indicating that tofogliflozin also influences the HPA axis [ 122 ]. Moreover, metformin, an insulin-sensitizer used as the first-line drug for treating type 2 diabetes, does not only lower plasma insulin and glucose levels, but also can reduce ACTH levels and cortisol [ 123 , 124 ].…”
Section: Can Hyperinsulinemia-induced Activation Of the Hpa Axis Be M...mentioning
confidence: 99%
“…Most of the studies were male predominant. Two studies did not provide data on hypertensive prevalence 18 , 25 . One study did not report data on mean HbA1c and mean BMI 24 .…”
Section: Resultsmentioning
confidence: 99%
“…One study did not report data on mean HbA1c and mean BMI 24 . Two studies did not report data on mean systolic and diastolic blood pressure 18 , 25 , while one study did not report data on mean eGFR 23 . Among the studies, six types of SGLT2i were used: empagliflozin, ipragliflozin, canagliflozin, dapagliflozin, tofogliflozin, and luseogliflozin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other researchers have also reported that the progression of carotid atherosclerosis was associated with serum or urinary cortisol levels [ 32 34 ]. Interestingly, a recent study revealed that administration of tofogliflozin decreased both serum ACTH and cortisol levels in patients with T2DM, indicating that tofogliflozin influences the hypothalamic–pituitary–adrenal pathway in this population [ 35 ]. Therefore, SGLT2 inhibitors may be related to the attenuation of carotid atherosclerosis via reduction of serum cortisol levels.…”
Section: Discussionmentioning
confidence: 99%